Known Triterpenes and their Derivatives as Scaffolds for the Development of New Therapeutic Agents for Cancer - Peron, Gregorio; Marzaro, Giovanni; Dall'Acqua, Stefano (Current Medicinal Chemistry, 2018)
Background: Plants produce several bioactive secondary metabolites whose are used as therapeutic agents to treat several diseases, among whom cancer. Triterpenes are secondary metabolites that exert inhibitory activity against multiple intracellular and extracellular targets in euchariotic cells. These targets are proteins involved in apoptosis, cell development and differentiation, angiogenesis, metastasis and inflammatory processes. The inhibition of their functions leads to decreased cellular growth, differentiation and migration, resulting in antitumor activity, as shown by several authors. Furthermore, during recent years synthetic triterpenoid derivatives have also been developed to implement potency and efficacy of starting compounds, allowing the obtainment of new agents having promising anticancer activity. Objective: In this review we report the latest results regarding anticancer activity of some of the most studied triterpenes in the field, as well as of their semi-synthetic derivatives, with the aim to summarize the role of triterpenes as molecular leads for the development of new classes of antitumor agents. Methods: We focused on the most recent literature regarding triterpenes in cancer treatment, highlighting the potential of developing new drugs starting from these natural compounds. Conclusion: Several “old” triterpenes as ursolic, betulinic and oleanolic acids were recently reconsidered as model compounds for the development of innovative anticancer agents. Their activity against proteins involved in tumor development enhances the opportunity to exploit these compounds as new multi-target therapeutic agents. Furthermore, the possibility to synthetize new compounds from their natural-occurring structures could be an alternative to overcome cellular resistance to drugs and could improve their therapeutic efficacy.
Keywords: bioactive secondary metabolites